2023
DOI: 10.1364/ao.479520
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz phase modulator based on a metal-VO2 reconfigurable metasurface

Abstract: Actively controlling the phase of a terahertz (THz) wave is of great significance for beaming, tunable focusing, and holography. We present a THz phase modulator based on an electrically triggered vanadium dioxide ( V O 2 ) reconfigurable metasurface. The unit cell of the device consists of two split-ring resonators embedded with a V O 2 ribbon. By ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[ 109a,149 ] For example, Li et al. [ 148b ] found that the vdW bond between the mica substrate and the VO 2 film was used to avoid the clamping effect, reduce the lattice effect of the film and the substrate, and reduce the heat conduction of the film to the substrate because of the weak lattice coupling, and finally reduce the trigger threshold and keep ideal Md.…”
Section: Progress In Vo2 Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 109a,149 ] For example, Li et al. [ 148b ] found that the vdW bond between the mica substrate and the VO 2 film was used to avoid the clamping effect, reduce the lattice effect of the film and the substrate, and reduce the heat conduction of the film to the substrate because of the weak lattice coupling, and finally reduce the trigger threshold and keep ideal Md.…”
Section: Progress In Vo2 Applicationmentioning
confidence: 99%
“…In addition, high modulation depth can be achieved by setting the metasurface structure to change the optical transmission of the device. [ 16d,148 ] In general, high modulation depth means that a large number of signals can be controlled, increasing the diversity of modulation. As shown in the Table 6, some current studies have achieved modulation depth of more than 99% at specific frequencies and 90% average modulation depth in a certain band.…”
Section: Progress In Vo2 Applicationmentioning
confidence: 99%